Photocatalytic efficiency of titanium dioxide immobilized on PVP/AAc hydrogel membranes: A comparative study for safe disposal of wastewater of Remazol Red RB-133 textile dye - Hoda S. Hafez; A. El-Hag Ali; M. S. A. Abdel-Mottaleb (International Journal of Photoenergy)
The paper reports on the photocatalytic efficiency of TiO2 nanoparticles immobilized on polyvinyl pyrrolidone/acrylic acid (PVP/AAc) copolymer hydrogels, which are prepared by means of γ-rays induced homo- and copolymerization. The efficiency of immobilized photocatalyst is tested on a commercial textile dye namely Remazol Red RB-133. The results are compared with photocatalytic efficiencies of different types of non supported TiO2 photocatalysts such as aqueous slurries of colloidal TiO2 prepared by sol-gel technique, and commercially available Degussa P25. Although less efficient than nonsupported ones, the hydrogel supported TiO2 photocatalyst has the practical advantages of easy separation and removal from the reactors. This makes it a viable technique for the safe disposal of textile wastewater into the water streams.